(untitled) (International Journal of Engineering and Computer Science, 2021)
Emergency services are highly needed for all in nowadays. Quick emergency services can save someone’s life. Urgency never comes with a prior indication. In real-world scenarios, getting such services and reporting is a real challenge. Emergency services are government agencies whose job it is to respond quickly to emergencies when they arise, including firefighters, police, medical services, blood bank service and ambulance service. These all are very essential and life-protected services for all people in society because without these services we can’t survive. We know that getting quick blood services, fire department etc. are very tough for us and we need these services which ensure urgent stabilization of the situation and transport to definitive care. In our busy life, for getting quick services we’ve made a software and for this every people will get all those essential services very easily and too fast. In this project, we have introduced a web application which provides the information of all emergency services and which can be accessed by all users 24 hours a day, 7 days a week. Some features will be available like finding nearby blood bank, medical services in whole night and from the police station to the fire department all in one place. Nowadays for this pandemic situation nobody knows when the problem will create. By this web-application everybody will get to know the all information from medical services to police station. Urgency never comes with a prior indication. We know that in real-world scenarios, survive is a big challenge for all and detecting such emergencies and reporting them is a real challenge. For society we want to provide quick emergency services and that’s why we’ve made it. So, we think this application will help all people.